Pengaruh Sistem Pengendalian Intern Pemerintah dan Whistleblowing System Terhadap Pencegahan Fraud Dengan Moralitas Individu Sebagai Variabel Moderasi Pada Dinas Sosial Provinsi Sumatera Utara - Susi Findiowaty; Eka Nurmala Sari; Zulia Hanum (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study was conducted to examine and analyze the effect of the government internal control system and whistleblowing on fraud prevention, with individual morality as a moderating variable. The study used an associative research approach. The data collection technique used was questionnaire distribution. The sampling technique used a quota sampling technique with 45 respondents. Path analysis using SEM PLS version 4 was used. Based on the results, it was concluded that the government internal control system has a positive effect on fraud prevention. This indicates that a better government internal control system will improve fraud prevention among employees at the Social Services of North Sumatra Province. The whistleblowing system has a positive effect on fraud prevention. This indicates that a better whistleblowing system will increase fraud prevention among employees at the North Sumatra Provincial Social Service. Individual morality moderates the effect of the government's internal control system on fraud prevention. This means that a better government internal control system, combined with individual morality, will increase fraud prevention among employees at the North Sumatra Provincial Social Service. Individual morality moderates the effect of the whistleblowing system on fraud prevention. This means that a better whistleblowing system, combined with individual morality, will increase fraud prevention among employees at the North Sumatra Provincial Social Service.